A polysaccharide from Dictyophora indusiata inhibits the immunosuppressive function of cancer‐associated fibroblasts. (8th October 2017) - Han, Shuyu; Ma, Chaoxiong; Hu, Minghua; Wang, Yuanyuan; Ma, Fangli; Tao, Ning; Qin, Zhihai
Abstract : Reversing the function of cancer‐associated fibroblasts (CAFs) may improve the efficacy of cancer therapy. Here, we isolated a novel polysaccharide from Dictyophora indusiata (ZSP4) and examined its effects on the function of prostate CAFs. The supernatant of prostate CAFs can stimulate the proliferation of immune cells and inhibit the growth of CD4+/CD8+ T cells. However, after ZSP4 stimulation, the functions of prostate CAFs were inhibited. The mechanism experiment shows that ZSP4 can stimulate prostate CAFs by down‐regulating the expression ofα‐smooth muscle actin . Polysaccharides extracted from Dictyophora indusiata stimulate the proliferation of immune cells and reverse the immune‐suppressive functions of prostate CAFs, shedding new light on the development of novel anticancer strategies. The endocrine therapy used to treat prostate cancer aims to eliminate androgenic activity from prostatic tissue; these therapies are painful and of poor therapeutic effect. In this study, we found that polysaccharides extracted from Dictyophora indusiata may affect the micro‐environment of tumours and inhibit the growth of the tumours. Our results suggest that polysaccharides may modulate negative immune regulation and enhance antitumour immunity, which is important for clinical therapy.